Nomogram to predict malignancy in branch duct type intraductal papillary mucinous neoplasms. Issue 38 (23rd September 2022) - Xu, Yisheng; Xie, Chunmei; Gao, Zhiqin; Zhang, Meihua; Zhan, Ming
Abstract : Prediction of malignancy in branch duct (BD)-type intraductal papillary mucinous neoplasms (BD-IPMNs) is difficult. In this retrospective study, we showed the performance of imaging biomarker and biochemical biomarker in identifying the malignant BD-IPMNs. A total of 97 patients with pathological proved BD-IPMNs were included in this study. Imaging data were collected from magnetic resonance imaging (MRI). Malignant BD-IPMNs were defined as those with high grade dysplasia and invasive carcinoma. There were 10 patients with malignant BD-IPMNs (10.3%). Significant difference was found in prevalence of mural nodule and tumor size >3.0 cm between patients with and without malignant BD-IPMNs (44.4% vs 3.1%, P < .01; 80.0% vs 33.3%, P < .01). Significant differences were observed in mural nodule and elevated carbohydrate antigen 19-9 (CA19-9) between patients with and without invasive carcinoma (40.0% vs 7.6, P = .05; 60% vs 15.3%, P = .04). Mural nodule and tumor size >3.0 cm were the independent associated factor for malignant BD-IPMNs. The odds ratio (OR) was 5.22 (95% confidence interval [CI]: 1.04–31.16) for mural nodule and was 6.80 (95% CI: 1.16–39.71) for cyst size >3.0 cm. The combined model of mural nodule and tumor size showed good performance in identifying malignant BD-IPMNs (area under the curve [AUC] = 0.82, 95%CI: 0.67–0.97). Our data show that mural nodule and cystic size can be used as predictor of malignancy in BD-IPMN. The predictive performance is acceptable.